Foresight on Demand (FoD) Impact of the COVID-19 Pandemic on European Consumer Behaviour - Foresight Study - Kimpeler Simone; Cuhls Kerstin; Freudenberg Charlotte; Giuffré Giovanna; Galvini Giorgia; Ricci Andrea; Marmora Loredana; Giesecke Susanne; Wasserbacher Dana; Heinonen Sirkka; Knudsen Mikkel Stein; Könnölä Totti (European Commission, 2025)
Over the course of the project, experts and stakeholders were repeatedly involved in order to jointly develop opportunities and risks for consumers, particularly vulnerable groups, and ideas for policy actions. The project served as a pilot project for the implementation of comprehensive strategic foresight in DG JUST and for building capacities to cope with future uncertainties. The identified trends and scenarios provide an overview of possible future developments in consumption after the COVID-19 pandemic, which can be addressed with the proposed ideas for policy actions for sustainable consumer protection and the strengthening of consumer rights for the green and digital transition.